On the structural-optical correlation of ZnO nanospheres synthesized using thermal evaporation technique - Fatin Farisha Alia, Azmi; Saifful Kamaluddin, Muzakir; Mohd Fakhrul Zamani, Kadir; Shujahadeen B., Aziz (Taylor & Francis, 2022)
Zinc oxide clusters of different sizes and geometrical shapes have been synthesized and characterized experimentally and theoretically. The ZnO cluster models have been built and presented to study the evolution of physico-chemical properties of the metal oxide semiconductor upon reduction of size. However, most of the theoretical models are lack of support from the experimental details. This article aims to correlate the geometry of the theoretical models with their optical properties. The ZnO thin films were synthesized by thermal evaporator at vacuum pressures of 5 × 10−5 Torr. Cluster models of the synthesized ZnO were built based on its crystal structure. The clusters were evaluated as realistic using geometry optimization, and harmonic frequency calculations at the level of B3LYP functional and lanl2dz basis set. We observed that the fabricated ZnO thin film was constructed by small ZnO spherical clusters, which revealed by the Field Emission Electron Microscopy (FESEM) . This observation is in good agreement with our theoretical simulations, which were established based on its crystal structure – characterized by the X-ray diffractometer.